“Aprendendo a ser diretora de escola sendo": um olhar para as aprendizagens de diretoras iniciantes - Lima, Carla Valeria Farias (2022)
The present dissertation focuses on the learning characteristics of beginning school principals. The 5 professionals participating in the research were approved in the public contest of tests and titles at the State Department of Education of São Paulo-SEDUC, in the year of 2018. The research question of the study was: How is the learning of beginning school principals characterized? This is an exploratory study, of a qualitative nature, based on the analysis of the prose (ANDRÉ 1983, 2018). The theoretical contributions of the research were: the context of school administration; the public school as a place of work, of learning through teaching, struggles and contradictions; characteristics of the beginning in the position, knowledge and permanent learning. The professional characteristics of the work of school administration in contemporary times, the trends for the training of principals and the challenges of work in the face of social demands in favor of an education that meets more emancipatory and democratic practices were analyzed. By means of interviews, empirical data related to the first years in the position were collected, which made it possible to glimpse situations of survival/hardships and discovery/delights, according to early career aspects (HUBERMAN, 2013) in three work domains (administrative, pedagogical and political), to raise aspects and specificities of the initial phase of the principals' work, such as the subjectivity of their practices, their difficulties, coping with everyday situations and overcoming difficulties, in a process of permanent training, revealing factors present in the school routine that impact on the learning process of the position, sometimes favoring, sometimes hindering the work of directors: routine activities; the unpredictability of situations; peer support; conflicts and challenges arising from interpersonal relationships; bureaucratic activities and the challenge of pedagogical work aiming at quality education. We conclude that there are numerous difficulties that mark this initial phase of the work of school principals, similarly to teachers, principals also start working in difficult schools, bureaucratic activities and relationships are the most challenging aspects and overcoming difficulties makes with them to remain in the position, leading them to learn how to be principals.